Effect of Counselling on Medication Adherence in Tb Patients with the DOTS Strategy: A Scoping Review - Kurnia, Anggraini Dwi; Ni’mah, Isna Hidayatun; Masruroh, Nur Lailatul; Melizza, Nur (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis; these bacteria can attack various organs especially the lungs. Lack of knowledge and awareness of the importance of taking medication which leads to poor patient adherence in treatment thus increases the risk of morbidity, mortality and drug resistance in TB patients. Providing counselling is an effort to increase patient’s knowledge and understanding to increase their compliance with medication. This study aims to determine the effect of counselling in increasing medication adherence to TB patients with the DOTS strategy through a literature review. This study used a literature study research method by examining 11 journals related to counselling in increasing medication adherence to TB sufferers. The data was collected by searching data based on article data published on the Google Scholar, Proquest, Pubmed, and EBSCOhost websites. Then the data were analyzed using descriptive analysis. The data was then assessed using the Joanna Briggs Institute (JBI) and data extraction was carried out. In 11 journals related to counselling in improving medication adherence to TB patients, it was found that 11 journals proved that there was an effect of counselling in increasing medication adherence of TB patients with the DOTS strategy. Counselling added to the DOTS strategy is effective in increasing medication adherence to TB patients compared to the DOTS strategy without counselling. There are several methods of providing counseling such as individual counseling, counseling with a psychological approach, telephone counseling, leaflet-based counseling, and counseling-based motivational interviewing. The conclusion of this study is that counselling can improve medication adherence to TB patients with the DOTS strategy. By providing counselling, it can increase the patient's knowledge and understanding so that it can change the patient's behavior to a better and positive direction, which is shown by the patients' behavior who adherence to TB medication.Tuberkulosis (TB) adalah penyakit menular yang disebabkan oleh bakteri Mycobacterium tuberculosis; bakteri ini dapat menyerang berbagai organ terutama paru-paru. Kurangnya pengetahuan dan kesadaran akan pentingnya minum obat yang menyebabkan rendahnya kepatuhan pasien dalam pengobatan sehingga meningkatkan risiko morbiditas, mortalitas dan resistensi obat pada pasien TB. Pemberian konseling merupakan upaya untuk meningkatkan pengetahuan dan pemahaman pasien untuk meningkatkan kepatuhannya dalam minum obat. Penelitian ini bertujuan untuk mengetahui pengaruh konseling dalam meningkatkan kepatuhan minum obat pada pasien TB dengan strategi DOTS melalui studi pustaka. Penelitian ini menggunakan metode penelitian studi kepustakaan dengan menelaah 11 jurnal terkait penyuluhan dalam meningkatkan kepatuhan minum obat pada penderita TB. Pengumpulan data dilakukan dengan mencari data berdasarkan data artikel yang dipublikasikan di website Google Scholar, Proquest, Pubmed, dan EBSCOhost. Kemudian data dianalisis dengan menggunakan analisis deskriptif. Data tersebut kemudian dinilai menggunakan Joanna Briggs Institute (JBI) dan dilakukan ekstraksi data. Pada 11 jurnal terkait konseling dalam meningkatkan kepatuhan minum obat pada pasien TB ditemukan 11 jurnal yang membuktikan adanya pengaruh konseling dalam meningkatkan kepatuhan minum obat pasien TB dengan strategi DOTS. Konseling dengan strategi DOTS lebih efektif dalam meningkatkan kepatuhan minum obat pada pasien TB dibandingkan dengan strategi DOTS tanpa konseling. Ada beberapa metode pemberian konseling seperti konseling individu, konseling dengan pendekatan psikologis, konseling telepon, konseling berbasis leaflet, dan wawancara motivasi berbasis konseling. Kesimpulan dari penelitian ini adalah penyuluhan dapat meningkatkan kepatuhan minum obat pada pasien TB dengan strategi DOTS. Dengan memberikan penyuluhan dapat meningkatkan pengetahuan dan pemahaman pasien sehingga dapat mengubah perilaku pasien ke arah yang lebih baik dan positif, yang ditunjukkan dengan perilaku pasien yang patuh minum obat TB.